Dedicator of cytokinesis 8 regulates signal transducer and activator of transcription 3 activation and promotes TH17 cell differentiation - Keles, Sevgi; Charbonnier, Louis Marie; Kabaleeswaran, Venkataraman; Reisli, Ismail; Genel, Ferah; Gulez, Nesrin; Al-Herz, Waleed; Ramesh, Narayanaswamy; Perez-Atayde, Antonio; Karaca, Neslihan E.; Kutukculer, Necil; Wu, Hao; et al. (Journal of allergy and clinical immunology, 2016)
The autosomal recessive hyper-IgE syndrome (HIES) caused by dedicator of cytokinesis 8 (DOCK8) deficiency shares clinical features with autosomal dominant HIES because of signal transducer and activator of transcription 3 (STAT3) mutations, including recurrent infections and mucocutaneous candidiasis, which are suggestive of TH17 cell dysfunction. The mechanisms underlying this phenotypic overlap are unclear. We sought to elucidate common mechanisms operating in the different forms of HIES. We analyzed the differentiation of CD4+ TH cell subsets in control and DOCK8-deficient subjects. We also examined the role of DOCK8 in regulating STAT3 activation in T cells. TH cell differentiation was analyzed by ELISA, flow cytometry, and real-time PCR measurements of cytokines and TH cell transcription factors. The interaction of DOCK8 and STAT3 signaling pathways was examined by using flow cytometry, immunofluorescence, coimmunoprecipitation, and gene expression analysis. There was a profound block in the differentiation of DOCK8-deficient naive CD4+ T cells into TH17 cells. A missense mutation that disrupts DOCK8 guanine nucleotide exchange factor (GEF) activity while sparing protein expression also impaired TH17 cell differentiation. DOCK8 constitutively associated with STAT3 independent of GEF activity, whereas it regulated STAT3 phosphorylation in a GEF activity–dependent manner. DOCK8 also promoted STAT3 translocation to the nucleus and induction of STAT3-dependent gene expression. DOCK8 interacts with STAT3 and regulates its activation and the outcome of STAT3-dependent TH17 differentiation. These findings might explain the phenotypic overlap between DOCK8 deficiency and autosomal dominant HIES.